Feasibility of high-resolution DWI of the healthy dental pulp in human using a hybrid TGSE BLADE sequence - Sittinger, Mia; Sandner, Christoph; Zhou, Kun; Mente, Johannes; Lauer, Arne; Özen, Ali C.; Vollherbst, Dominik; Breckwoldt, Michael O.; Bendszus, Martin; Heiland, Sabine; Hilgenfeld, Tim (Scientific reports, 2025)
Clinical evaluation of the human dental pulp is limited to imprecise, subjective methods, necessitating the development of an accurate and objective diagnostic parameter. Diffusion-weighted imaging (DWI) could address this gap; however, no in vivo data are available. To illustrate the feasibility of DWI imaging of the human pulp and to investigate physiological patterns. A turbo gradient spin echo (TGSE) BLADE diffusion MRI sequence was optimized for dental pulp imaging in three volunteers, defining an optimal b-value range and assessing intraindividual fluctuations at 3 T. Apparent diffusion coefficient (ADC) values were calculated in 18 participants using the 2-point and 7-point methods in 329 healthy teeth, analyzing data according to tooth and jaw type. Statistical analysis was performed using Kruskal-Wallis, Wilcoxon signed-rank-test, and one-way ANOVA. Mean pulp ADCs (± SD) for the 2-/7-point methods were 1.219 ± 0.340 / 1.242 ± 0.297 × 10−9 m2/s (p ≤ 0.0001), with intraindividual variations of 0.159 × 10−9 m2/s. Minor but significant differences were observed between tooth types for maxillary premolars vs. maxillary incisors/canines, mandibular canines, and maxillary incisors vs. molars (ADC difference range: 0.209-0.272 × 10−9 m2/s; p-values: 0.0017-0.0473). In vivo assessment of the dental pulp by DWI is feasible and reliable using the TGSE BLADE sequence. Reference ADC values were established, with no substantial differences between jaw and tooth types, indicating that the ADC is a stable intraindividual parameter here. These findings may substantially improve the diagnostic evaluation of pulp diseases to minimize over- and undertreatment.
Gesehen am 27.01.2026